Persona y fundamento en el Leviatán de Hobbes - Galimidi, José (2020)
“Person and foundation in Hobbes’ Leviathan”. Personification is a central device in the logic of statehood displayed by Hobbes’s Leviathan. On the one hand, it appears as an indispensable concept for understanding all the forms of intersubjective encounter, both cooperative and agonal, that can occur in any sphere, private or public. On the other, it intervenes in the generation of the power of absolute sovereignty and in the capillarity of each instance of the civil life in which it is effectively present, through its officials, judges and emissaries. Like all the conceptual figures offered by Hobbes, personification connotes ambiguities and complexities that problematize the domain structures that it seeks to legitimize. Our work proposes an analysis of the articulation potential of this concept with attention to the Hobbesian foundation of sovereignty and of the state building. We also understand that the representational device offers an additional element of consistency to Hobbes’ political model, insofar as it links it to the theological dimension through the representation of the divine person which corresponds to the office of sovereignty